2020
DOI: 10.1111/jog.14247
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about the human papillomavirus among high school and university students a comprehensive questionnaire study from Southeast Turkey

Abstract: Aim:To investigate the level of knowledge among high school and university students about the human papillomavirus (HPV) and its vaccine. Methods: Our study included 3039 Grade 9-12 students from 12 high schools and university students enrolled in medical and non-medical departments. The students completed a 30-item questionnaire, which included three demographic items (sex, age and grade) and measured knowledge regarding HPV, HPV vaccine, smear test and cervical cancer. Students responded by selecting one of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
(29 reference statements)
0
7
1
Order By: Relevance
“…In contrast to the current study findings, studies performed in Turkey revealed that university students mostly adopt the internet, television and print media as their source of information on sexual health (Bayramoğlu Tepe & Ozcorekci, 2020;Borlu et al, 2016). Further, a study from Greece that included young women of ages 17-24 reported that 69.7% had sufficient information regarding HPV and 95.9% knew about the vaccine (Michail et al, 2014).…”
Section: Sources Of Information Used By Female Undergraduates To Acqu...contrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the current study findings, studies performed in Turkey revealed that university students mostly adopt the internet, television and print media as their source of information on sexual health (Bayramoğlu Tepe & Ozcorekci, 2020;Borlu et al, 2016). Further, a study from Greece that included young women of ages 17-24 reported that 69.7% had sufficient information regarding HPV and 95.9% knew about the vaccine (Michail et al, 2014).…”
Section: Sources Of Information Used By Female Undergraduates To Acqu...contrasting
confidence: 99%
“…Having more knowledge among Medical and Allied Health Science undergraduates specially among nursing students has been found in studies conducted elsewhere (Bayramoğlu Tepe & Ozcorekci, 2020;Borlu et al, 2016;Yam et al, 2017). High level of awareness has shown a correlation with higher educational levels as well (Borlu et al, 2016).…”
Section: Sources Of Information Used By Female Undergraduates To Acqu...mentioning
confidence: 74%
“…Moreover, medical students more commonly used single-use masks and wore face protection for longer periods of time [25]. This is not surprising, as the differences in health-related attitudes and behaviors between medical and non-medical students have been previously documented [26][27][28]. The criterion that non-medical students complied significantly better with was the disposure of single-use masks after their use at work.…”
Section: Discussionmentioning
confidence: 90%
“…It was documented previously that the health-related attitudes, behaviors, and practices differ between medical and non-medical students ( 12 ). Moreover, it was observed that medical students used face masks more commonly, for longer time periods, and less frequently reused the disposable masks ( 13 ).…”
Section: Discussionmentioning
confidence: 99%